The uneven foundations of a just transition for workers: a UK perspective - Reay, Dave (Frontiers in Climate, 2024)
Assessments of the workforce impacts of net zero transitions have largely focussed on job losses, gains and net changes for a particular industry, sector or state. While improved projections of quantitative changes are important, understanding the impacts of these changes on the diversity of the future workforce is arguably even more crucial in ensuring employment policy delivers a just transition for all workers. Using the example of the UK we illustrate the risk that new job creation in the transition to net zero by 2030 will perpetuate and further magnify workforce inequalities. We then discuss how national and international initiatives are attempting to mitigate these risks, with particular reference to the United Nations Framework Convention on Climate Change work programme on Just Transition Pathways and its potentially pivotal role in informing and supporting national workforce strategies for climate action that have equality, diversity and inclusion at their heart.